A blueprint for international marketing: Reaching audiences in the digital era. Issue 4 (27th February 2020) - Unknown
Abstract : Purpose of this paper: Reviews the latest management developments across the globe and pinpoints practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: As we start a new decade in 2020, it is inevitable that we look back at the last decade and forward to the next ten years to try and gain some perspective. In terms of marketing, it is one of those areas where it is difficult to imagine a period of greater change in terms of how quickly things have developed. In 2010, social media was in its infancy – Twitter had 30 million active monthly users compared to over 300 million by the end of the decade, and Instagram only appeared for the first at the end of that year. For marketing, and certain international marketing, it is as if the whole world opened up through new channels, and perhaps more importantly, those channels were free to use an audience becoming quickly addicted to their mobile phones. For many firms, it must have felt like a tap was suddenly being turned on through which their messaging could come gushing out. Practical implications: Provides strategic insights and practical thinking that have influenced some of the world's leading organizations. What is original/value of paper?: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.